Deleuze e a univocidade do Ser: um novo agenciamento para uma filosofia da diferença - Favreto, Elemar Kleber (2007)
The present work has for main objective the Deleuze's question concerning the unique sense of Being. At first, the present research approaches the different agencies done by Deleuze of the principal authors of Platonism, thought that constituted the bases of the representation and transcendence through four roots: identity, similarity, analogy and opposition. Next, the philosophy that, according to Deleuze, can still bring us an interpretation of not-Being as negative, or better, that can still bring us the Nihilism as form of thought is negotiated. In a third moment, the Deleuze's agency reports the main philosophies that constitute what he called "moments of the unique sense", such moments characterize the main theories that oppose the transcendence and the representation as principles, invoking the immanence and the repetition as their principal weapons. Finally, the horizon of the Deleuze's ontology that understands an only sense of Being is accomplished, antecipating a vast field of analysis that leads us to think the sense as an event, the Being as expression and the disjunctive synthesis as the assertion of Being.